PENINGKATAN KUALITAS SUMBER DAYA MANUSIA MELALUI PELATIHAN PRANATACARA BERBAHASA JAWA BAGI KADER MUDA MUHAMMADIYAH PONOROGO - Harsono, Jusuf; Abidin, Nurul; Chamidah, Siti; Sugianto, Alip (LPPM Universitas Bina Bangsa, 2024)
Javanese language Pranatacara training was chosen because currently there are many young people who rarely speak Javanese well among the Young Muhammadiyah Ponorogo cadres. Based on these problems, this service is an effort to bridge the needs of young cadres to improve the quality of Human Resources with Pranatacara training. The method used is learning by doing, learning by doing, namely providing theory about the concept of pre-events and practicing it directly. As a result, participants who previously did not understand the theory of good event management became more understanding, and those who previously felt less confident because they became more confident after knowing the knowledge gained from the training